PENGARUH RASIO PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN MELALUI EARNING PER SHARE PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - WIE SHE WUDJUD; SANTY AJI SITOHANG (JURNAL ILMIAH SIMANTEK, 2019)
This research aims to test and analyse the influence of (1) Return On Asset on the dividend policy on manufacturingcompanies on the Indonesia Stock Exchange. (2) Earning Per Share against dividend policy in manufacturing company inIndonesia Stock Exchange. (3) Return On Asset to Earning Per Share against the manufacturing company on the IndonesianStock Exchange (4) whether Earning Per Share is a perfect mediation or partial mediation variable on the influence of ReturnOn Asset to the dividend policy on manufacturing companies on the Indonesia Stock Exchange. The object of this researchis a manufacturing company listed on the Indonesia Stock Exchange period 2015-2016 for 143 companies. Samplesselected by survey method. From the survey method, the number of companies that can be used as samples as many as 25companies. Data source is obtained from the official website of Indonesia Stock Exchange at www.idx.co.id. The analyticaltechniques used were the Causal Step method developed by Baron and Kenny. The results of the study Show (1) Return OnAsset is positively and significantly impacted by the dividend policy of the manufacturing company on the Indonesia StockExchange period 2015-2016. (2) Earning Per Share affects the dividend policy on manufacturing companies of the IndonesiaStock Exchange period 2015-2016. (3) Return On Asset is influential on Earning Per Share in manufacturing companies ofIndonesia Stock Exchange period 2015-2016. (4) Earning Per Share is a partial mediation in the influence of Return OnAsset to the dividend policy on manufacturing companies on the Indonesia Stock Exchange period 2015-2016.